The demographic features of fatigue in the general population worldwide: a systematic review and meta-analysis - Yoon, Ji-Hae; Park, Na-Hyun; Kang, Ye-Eun; Ahn, Yo-Chan; Lee, Eun-Jung; Son, Chang-Gue (Frontiers in Public Health, 2023)
Background: Fatigue is one of the most common subjective symptoms that impairs daily life and predict health-related events. This study aimed to estimate the prevalence of fatigue in the global population.Methods: PubMed and the Cochrane Library were used to search for relevant articles from inception to December 31, 2021. Studies with prevalence data of fatigue in the general population were selected and reviewed by three authors independently and cross-checked. Regarding subgroups, adults (≥18 years), minors (<18 years), and specific occupation population (participants in each study being limited to a specific occupational group), and fatigue types and severity, meta-analysis was conducted to produce point estimates and 95% confidence intervals (95% CI).Results: From the initial 3,432 studies, 91 studies accounting for 115 prevalence data points (623,624 participants) were finally selected. The prevalence of general fatigue (fatigue lasting less than 6 months, or fatigue of unspecified duration) was 20.4% (95% CI, 16.7-25.0) in adults, 11.7% (95% CI, 5.2-26.6) in minors, and 42.3% (95% CI, 33.0-54.2) in specific occupations. Chronic fatigue (fatigue lasting more than 6 months) affected 10.1% (95% CI, 8.2-12.5) of adults, 1.5% (95% CI, 0.5-4.7) of minors, and 5.5% (95% CI, 1.4-21.6) of subjects in specific occupations. There was an overall female-predominant prevalence for all subgroup analyses, with a total odds ratio of 1.4 (95% CI, 1.3-1.6). Regarding the severity and presence of medical causes, the total prevalence of moderate fatigue (14.6% [95% CI, 9.8-21.8]) was 2.4-fold that of severe fatigue (6.1% [95% CI, 3.4-11.0]), while unexplained fatigue (fatigue experienced by individuals without any underlying medical condition that can explain the fatigue ) was approximately 2.7-fold that of explained fatigue (fatigue experienced by individuals with a medical condition that can explain the fatigue); as proportion of 40.0% of physical, 8.6% of mental, and 28.4% of mixed cause.This study has produced the first comprehensive picture of global fatigue prevalence in the general population, which will provide vital reference data contributing to fatigue-related research, including the prevention of diseases.